My shining archipelago. - Ansel, Talvikki, 1962- (Yale series of younger poets, 1997)
The winner of the 1996 Yale Series of Younger Poets competition is Talvikki Ansel for My Shining Archipelago. "Ansel`s poetry is refreshingly original," says the distinguished poet and contest judge James Dickey. "She renders the heat, the closeness, the mystery, and the terrible fear of the undisclosed, the lurking, the waiting to happen. This is true imagination, true craft." Flemish BeautyYesterday, all winter, I had not thought of pears, considered: pear. The tear-shaped, papery core, precise seeds. This one channeled through with worm tunnels. Bruises, a rotten half-- sometimes there's nothing left to drop into the pot. That phrase I could have said: "you still have us ..." The knife slides easily beneath the skins, top to base, spiraling them away. The insubstantial us. It could as well be the pear talking to the river, turning to the grass ("you still have us"). Besides, it's just me a pear in my hand (the slop bucket full of peels)--and sometimes, yes, that seems enough: a pear-- this larger one, yellow-green, turning to red: "Duchess" maybe, "Devoe," or what I want to call it: "Flemish Beauty." When I can't sleep, I'll hold my hand as if I held a pear, my fingers mimicking the curve. The same curve as the newel post I've used for years, swinging myself up to the landing, always throwing my weight back. And always nails loosening, mid-bound